เส้นทางวัฒนธรรมถนนโบราณสายเชียงใหม่-ลำพูน เพื่อการเรียนรู้และท่องเที่ยวเชิงวัฒนธรรม - เพียงพร คำมูล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
Chiang Mai - Lamphun Road located on Highway 106 is regarded as the ancient thoroughfare between communities since the reign of King Rama V. Dominant feature of the road is rubber trees lining up along the 15-kilometer road. As there have been Lanna people living from the past, valuable and unique cultural heritage of Lanna remains. However, the growth and development of the community nowadays impact lifestyles of Lanna residents. This study, thus, aims to propose the methods of learning and cultural tourism along the ancient road Chiang Mai – Lamphun as well as promote this road to be the precious cultural heritage of the community. Therefore, the residents will have a sense of pride and realize the important of maintaining this cultural heritage. The study is quantitative research to which the interdisciplinary study is employed. The findings are presented through the description. According to the study, there are 50 interesting cultural landmarks along the Chiang Mai - Lamphun Road. The 32 landmarks are selected to be the path of learning and cultural tourism. They are divided into two types including (1) the form of learning and cultural tourism which can be categorized due to their type of heritage namely, the community market and handicraft as well as the temples and historic sites and (2) the form of learning and cultural tourism focusing on the overview of Chiang Mai - Lamphun Road. Besides, this study proposes the methods of learning and tourism management in which the residents can get involved and the media concerning learning and cultural tourism along this route.